Implementasi Program Permakanan Surabaya Sebagai Upaya Pemenuhan Kebutuhan Pangan Masyarakat Surabaya pada Masa Pandemi Covid-19 - Nikmah, Syarifah (Pusat Penelitian dan Pengabdian pada Masyarakat Sekolah Tinggi Ilmu Administrasi (STIA) Mataram, 2023)
In an effort to meet food needs during the Covid 19 pandemic, the Mayor of Surabaya provided food needs to the community. The aim of this study was to find out how the implementation of the Surabaya Food program is an effort to help fulfill food needs for the people of Surabaya, especially during the Covid 19 pandemic. The Surabaya Food Program is a food delivery program for the Food program targets, namely the elderly, people with disabilities, and orphans who are poor. poor and abandoned as well as communities affected by Covid 19. In the implementation of the Food program there are problems, one of which is complaints from the people in the Rungkut Surabaya area about Food for the elderly that there has been a reduction in food distribution rations during the Covid 19 pandemic, there is also the problem that there are elderly people in Surabaya who have not received any assistance during the Covid 19 pandemic. This research uses a descriptive research type with a qualitative approach. This research design uses a systematic literature review or literature review where information and data are taken from books, journals, online articles, online platforms, and official government portals. For the analysis technique using an interactive model from Miles and Huberman namely data collection, data processing, data presentation, and drawing conclusions.